Exploring Gender Gaps: How Nigerian Micro Business Owners Use Mobile Apps for Business - (:unkn) unknown (My University, 2020)
This exploratory study examined how men and women who own micro businesses in Lagos, Nigeria, use mobile apps for business from Amartya Sen’s capability approach perspective and quantitative research methods. The two key findings suggest that women micro business owners make more use of mobile apps compared to men, and that they tend to exit micro businesses as they grow older indicating a possible influence of patriarchy in African contexts. Specifically, women seized opportunities presented by mobile apps to acquire capabilities to function; and they adapt mobile apps to enhance their wellbeing and freedom despite the restrictions and responsibilities in the patriarchal environments typical of low-income countries. The insignificant gender gap in certain mobile app usages presents new perspectives to debates on gender (economic) gaps, inequality, women empowerment, and technology uptake in low-income country contexts.
Keywords: African Research